Cambodia - Poverty and Social Impact of the Global Economic Crises : Using the Past to Plan for the Future - World Bank (Washington, DC, 2013)
This paper discusses the progress made by Cambodia from the early 90s to 2007, in reduction of poverty incidence. Reduced poverty occurred in both urban and rural areas, and was experienced by rich and poor, and by men and women. Households, including those in the poorest groups, have improved their housing quality, increased ownership of motorbikes, televisions, and mobile phones, and are better able to access and afford schools and healthcare. However, the study warns about complacency, because poverty is still pervasive in the rural areas, and a multi-dimensional approach is needed to tackle it. The gap in income and opportunities remains wide between the rich and the poor, the urban and rural regions and more importantly, within the rural areas themselves. The report concludes that it is clear that Cambodia has made substantial improvements in the information systems available to guide public policy. The next step is to improve coordination among the information sources and develop a national information system that allows for the combined use of information and the setting of priorities based on an assessment of needs and existing gaps in the country. To address these problems, an evaluation of the quality, relevance and use of information produced in Cambodia is necessary in order to establish standards and identify areas of improvement.